Social skills in sport: a scope review (Research, Society and Development, 2021)
This research is a scoping review protocol, which aims to explore in the available literature, how social skills are approached in sport, and their possible influences on the athlete's affective and emotional cognitive adaptation. For this, PubMed, Web of Science, Scopus and Pepsic / Lilacs databases will be used, using the mnemonic PCC (Population, Context and Concept), the selected terms were, athletes, social skills and sport, being interconnected by the Boolean operator E. Literature from the last 5 (five) years will be considered, in Portuguese, Spanish and English. For its construction and methodological structuring considered considered the following: kind of study; identification of the research question; identification of relevant studies; selection of studies; information mapping; presentation of results and ethical aspects. Relevant information will be stored in the Excel application, for the analysis and preparation of tables and other graphic resources for displaying data, results and subsequent results.